Keterangan Pelatihan Pembukuan, Pencatatan Dan Pelaporan Keuangan Sederhana Menuju Entrepreneur Modern, Inovatif Dan Unggul Kepada Karang Taruna - Januar Eky Pambudi; Hendra Galuh Febrianto; Indra Gunawan Siregar; Basuki Basuki; Mikrad Mikrad; Priyo Susilo (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
Karang Taruna as a social organization as well as a forum and means for the development of every member of society which grows and develops on the basis of social awareness and responsibility from, by and for the community, especially the young generation in the village/sub-district area, is primarily engaged in the field of social welfare business.